2020
DOI: 10.3390/jcm9124087
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Vessel Density as a New Vascular Biomarker in Multisystem Involvement in Fabry Disease: An Optical Coherence Tomography Angiography Study

Abstract: In this study, we evaluated the possible relationship between the changes in retinal vessel density (VD) by optical coherence tomography angiography (OCTA) and the vascular alterations involving renal, cardiovascular and central nervous systems in patients affected by Fabry disease (FD). In 50 FD patients, the retinal superficial capillary plexus (SCP) and deep capillary plexus (DCP) in macular region were evaluated by OCTA examination. The patients also underwent a brain magnetic resonance imaging scan, renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A recent study by Cennamo et al ( 40 ) evaluated the relationship between the changes in retinal vessel density by OCTA and the vascular alterations involving renal, cardiovascular, and central nervous systems in FD patients: the vessel density of SCP and DCP was inversely related to echocardiographic parameters (early mitral inflow peak velocity to early diastolic mitral annulus peak velocity ratio, left atrial volume index, interventricular septal thickness, global longitudinal strain, and systolic pulmonary artery pressure); however, no relationship was found, with a multivariate analysis, between OCTA parameters and kidney function and neuroradiological signs of central nervous system involvement.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study by Cennamo et al ( 40 ) evaluated the relationship between the changes in retinal vessel density by OCTA and the vascular alterations involving renal, cardiovascular, and central nervous systems in FD patients: the vessel density of SCP and DCP was inversely related to echocardiographic parameters (early mitral inflow peak velocity to early diastolic mitral annulus peak velocity ratio, left atrial volume index, interventricular septal thickness, global longitudinal strain, and systolic pulmonary artery pressure); however, no relationship was found, with a multivariate analysis, between OCTA parameters and kidney function and neuroradiological signs of central nervous system involvement.…”
Section: Discussionmentioning
confidence: 95%
“…One study reported vessel density as increased in the deep capillary plexus and decreased in the superficial capillary plexus [ 63 ]. Another study found no association between any retinal vessel density metrics and Fabry disease [ 62 ]. Regarding foveal avascular zone area, three papers [ 53 , 60 , 64 ] reported no difference between Fabry cases and controls and two papers [ 37 , 61 ] reported enlargement in affected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in A v provide information on vascular integrity 14–18 . Retinal vascular density changes as a possible biomarker have been reported in several other diseases such Alzheimer diseases, mild cognitive impairment, Fabry disease and diabetes mellitus 26–28 . Our control subjects T v ranged from approximately 1.11 to 1.15 pixel/pixel.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 , 18 Retinal vascular density changes as a possible biomarker have been reported in several other diseases such Alzheimer diseases, mild cognitive impairment, Fabry disease and diabetes mellitus. 26 , 27 , 28 Our control subjects T v ranged from approximately 1.11 to 1.15 pixel/pixel. Higher T v was observed in arteries (1.17 ± 0.04) and veins (1.17 ± 0.04) of PAH subjects, indicating that retinal T v in treated PAH patients may be abnormally increased.…”
Section: Discussionmentioning
confidence: 99%